Development of antimicrobial coating by later-by-layer dip coating of chlorhexidine-loaded micelles - Supreeda Tambunlertchai (2018)
© 2017, Springer Science+Business Media New York. Layer-by-layer (LbL) dip coating, accompanying with the use of micelle structure, allows hydrophobic molecules to be coated on medical devices’ surface via hydrogen bonding interaction. In addition, micelle structure also allows control release of encapsulated compound. In this research, we investigated methods to coat and maximize the amount of chlorhexidine (CHX) on silicone surface through LbL dip coating method utilizing hydrogen bonding interaction between PEG on micelle corona and PAA. The number of coated cycles was varied in the process and 90 coating cycles provided the maximum amount of CHX loaded onto the surface. In addition, pre-coating the surface with PAA enhanced the amount of coated CHX by 20%. Scanning electron microscope (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to validate and characterize the coating. For control release aspect, the coated film tended to disrupt at physiological condition; hence chemical crosslinking was performed to minimize the disruption and maximize the release time. Chemical crosslinking at pH 2.5 and 4.5 were performed in the process. It was found that chemical crosslinking could help extend the release period up to 18 days. This was significantly longer when compared to the non-crosslinking silicone tube that could only prolong the release for 5 days. In addition, chemical crosslinking at pH 2.5 gave higher and better initial burst release, release period and antimicrobial properties than that of pH 4.5 or the normal used pH for chemical crosslinking process.